Association of Depression to Age, Trimester, Gravida, Number of Live Children and Two or More Daughters and Having No Son in Currently Pregnant Females at Bahawalpur (Medical Forum Monthly, 2022)
Objective: To find out association of depression to age, trimester, gravida, number of live children and two or more daughters and having no son in currently pregnant females at Bahawalpur.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the antenatal clinic at Gynaecology and Obstetrics OPD at Bahawal Victorial Hospital, Bahawalpur during month of July, 2020.Materials and Methods: This study involving 150 pregnant women aged 18-47 years who were attending antenatal clinic at Gynaecology and Obstetrics OPD at Bahawal Victorial Hospital, Bahawalpur. This hospital is a tertiary care facility with large catchment area. Specific to our study is that we excluded all the patients having history of any psychiatric illness and physical illness having some association with depression before the start of current pregnancy. So that we may be able to find out the specific association of depression with current pregnancy.Results: Out of 150 pregnant women 23 were found having depression. This is 15.33%. Out of these 23 pregnant women 21 had mild to moderate depression, 2 had severe depression. No patient was having very severe depression. 50% of pregnant women belonged to age group 18-27 years and out them 24% (n=18) had depression. As regard trimester clarification, 1st trimester patients had 22.22% (n=10) patients of depression.Conclusion: It is important to diagnose and treat depression in pregnant females.